The Influence of Cooperative Studies on the Scientific Attitude and Science Learning Outcomes of Fourth Grade Elementary School Students - Ni Made Putri Dwi Apriliani; I Made Citra Wibawa; Ida Bagus Putu Arnyana (Universitas Pendidikan Ganesha, 2026)
The low quality of science learning, which is still dominated by the lecture method, has resulted in weak conceptual understanding and poor scientific attitudes among students. This research aimed to examine the different effects of Group Investigation (GI) and Student Teams Achievement Division (STAD) cooperative learning models on the scientific attitudes and science learning outcomes of fourth-grade elementary school students. A quantitative approach with a quasi-experimental design was utilized in this study. Data collection instruments included a scientific attitude questionnaire covering indicators such as curiosity and critical thinking, as well as a validated multiple-choice test for learning outcomes. Data were analyzed using inferential statistics through mean difference tests after meeting the requirements for normality and homogeneity. The results indicated significant differences in effectiveness between the two models. The Group Investigation model proved to be more effective in improving students' scientific attitudes, achieving an average score of 85.42 compared to the STAD model, which obtained 78.63. This was attributed to independent investigation activities and in-depth discussions within the GI model. Conversely, the STAD model was superior in enhancing student learning outcomes with an average score of 88.15 compared to the GI model at 82.74. The group and individual accountability within STAD encouraged more optimal concept mastery. The selection of a cooperative learning model must be adjusted to the focus of the desired learning objectives, whether it is the development of scientific attitudes or the mastery of academic concepts.